Combustion behaviors and kinetics of sewage sludge blended with pulverized coal: With and without catalysts. (April 2018) - Wang, Zhiqiang; Hong, Chen; Xing, Yi; Li, Yifei; Feng, Lihui; Jia, Mengmeng
Graphical abstract: Highlights: High mass percentage of SS resulted in a great decrease in index S of the blends. The combustion behaviors and kinetics of the blends with catalysts were studied. All the catalysts improved the combustion performance of the blended fuel. All the catalysts reduced the activation energy needed to combustion reaction. Fe2 O3 was an optimal option for catalytic combustion among the tested catalysts. Abstract: The combustion behaviors of sewage sludge (SS), pulverized coal (PC), and their blends were studied using a thermogravimetric analyzer. The effect of the mass ratio of SS to PC on the co-combustion characteristics was analyzed. The experiments showed that the ignition performance of the blends improved significantly as the mass percentage of SS increased, but its combustion intensity decreased. The burnout temperature ( T b ) and comprehensive combustibility index ( S ) of the blends were almost unchanged when the mass percentage of SS was less than 10%. However, a high mass percentage of SS (>10%) resulted in a great increase in T b and a notable decrease in S . Subsequently, the effects of different catalysts (CaO, CeO2, MnO2, and Fe2 O3 ) on the combustion characteristics and activation energy of the SS/PC blend were investigated. The four catalysts promoted the release and combustion of volatile matters in the blended fuels and shifted their combustion profiles to a low temperature. In addition, their peak separating tendencies were obvious at 350–550  C, resulting in high peak widths. All the catalysts improved combustion activity of the blended fuel and accelerated fixed carbon combustion, which decreased the ignition temperature and burnout temperature of the fuels. CeO2 had the best catalytic effects in terms of the comprehensive combustion performance and activation energy, followed closely by Fe2 O3 . However, the rare-earth compounds are expensive to be applied in the catalytic combustion process of SS/PC blend at present. Based on both catalytic effects and economy, Fe2 O3 was potentially an optimal option for catalytic combustion among the tested catalysts.